Intensitas Serangan Kutu Kebul pada Tanaman Tomat dengan pemberian Pestisida Nabati Berbahan Dasar Daun Tembakau : Intensity of Whiteflies Attacks on Tomato with The Application of Tobacco-Based Botanical Pesticides - Safitri, Betari; Putri, Sekar Utami; Febria, Dila; Darma, Wika Anrya (Gontor Agrotech Science Journal, 2024)
Whiteflies are the main insect pests of Solanaceae plants, especially tomatoes. The need for tomatoes has not been met due to fluctuating production. Increasing tomato production to meet national needs can be done by controlling these two main insect pests. Control can be done using vegetable pesticides. These ingredients include tobacco leaves, citronella leaves, and Javanese chilies. This research was carried out in June - August 2024 at the Lampung State Polytechnic practicum area. The study used a randomized block design with 6 treatments and 4 replications. The six treatments consisted of six plant-based pesticide compositions based on tobacco leaves. The composition of the botanical pesticide made is A. 100% tobacco leaves, B. 50% tobacco leaves + 50% citronella leaves, C. 75% tobacco leaves + 25% citronella leaves, D. 50% tobacco leaves + 50% Javanese chili, E. 75% tobacco leaves + 25% Javanese chili, and F. 35% tobacco leaves + 35% citronella leaves, and 30% Javanese chili. The results obtained in this study were that all tobacco-based botanical pesticide treatments could reduce the whitefly population by 100%. No composition is most effective in suppressing whitefly populations on tomato plants.